2021
DOI: 10.1155/2021/8655499
|View full text |Cite
|
Sign up to set email alerts
|

Positioning of the Moving and Static Contacts of the Switch Machine Based on Double-Layer Mask R-CNN

Abstract: With the continuous development of rail transit, the maintenance of the switch machine becomes more and more important, and the contact depth of the moving contact and static contact in the switch machine is a key part of it. At present, the manual measurement method is the main measure of contact depth, which has the problems of low efficiency and strong subjectivity. The measurement of contact depth based on machine vision includes two steps: moving and static contact positioning and distance conversion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…As most recent studies have focused on object detection, few of them present the applications for switch machines. Yin et al [12] attempt to detect the pillar of switch machines with two networks; this is a similar application to our work. Therefore, the algorithm proposed by Yin et al [12] is selected for the comparison.…”
Section: Experimental Results Of the Access Depthmentioning
confidence: 59%
See 4 more Smart Citations
“…As most recent studies have focused on object detection, few of them present the applications for switch machines. Yin et al [12] attempt to detect the pillar of switch machines with two networks; this is a similar application to our work. Therefore, the algorithm proposed by Yin et al [12] is selected for the comparison.…”
Section: Experimental Results Of the Access Depthmentioning
confidence: 59%
“…Yin et al [12] attempt to detect the pillar of switch machines with two networks; this is a similar application to our work. Therefore, the algorithm proposed by Yin et al [12] is selected for the comparison. The experimental results of the proposed algorithm, Yin et al [12] and Yolo, are shown in Figure 16.…”
Section: Experimental Results Of the Access Depthmentioning
confidence: 59%
See 3 more Smart Citations